Comparative analysis of continuous cropping tolerance and nutrient status of three types of sweet potatoes - Chen, Danyan; Jiang, Xiaorui; Xu, Xianju; Wang, Jidong; Zhang, Yongchun; Ma, Jingze; Zhang, Qun; Gao, Tianrui; Xu, Chenxi; Li, Shilong; et al. (International Journal of Agricultural and Biological Engineering, 2025)
Sweet potato varieties exhibited distinct feedback mechanisms in response to continuous cropping obstacles (CCO). This study evaluated the tolerance to CCO (TCCO) among three types (fresh, purple, and starch), each comprising five varieties, cultivated in a 16-year CCO plot (CCp) and adjacent non-continuous cropping plots (NCCp) in China. Yield, resistance coefficient (kY, yield ratio between CCp and NCCp), and nitrogen (N), phosphorus (P), and potassium (K) contents and relative accumulation (kN, kP, kK, similar to kY) in chunks or stem vines, were analyzed. Significant differences (p<0.05) in yield and nutrient contents were observed among all varieties and types. Four varieties (purple: Xu A1-144, Xu D9-123, and starch: Shang 19, Zhe 13) exhibited kY>1.0, indicating higher yields under CCp. Nutrient imbalance—particularly enhanced N uptake, was associated with CCO susceptibility. Fresh and purple chunks preferentially accumulated N, P and K, respectively, while starch varieties plants strongly absorbed more K. Under NCCp, chunks nutrient levels were correlated with multiple elements in stem vines. Under CCp, each chunk nutrient was primarily affected only by its homologous elements in stem vines. Notably, stem vine kK positively correlated with yield under CCO (r=0.34, p<0.05), and stem vines kN significantly correlated with both chunks kN and stem vines kK (p<0.05). Starch sweet potatoes demonstrated the most balanced NPK absorption for TCCO, with yield and nutrient absorption advantages. TCCO was closely linked to efficient and coordinated N–K absorption, regulated by genetic traits and soil nutrient status. Imbalanced NPK ratios and hindered K absorption played a central role in CCO. Strategies focusing on K management and breeding varieties with inter-organ nutrient coordination abilities could enhance the stress resistance of sweet potato production systems. These findings provide genetic resources and insight into the mechanism of CCO tolerance in sweet potato. Key words: sweet potato type; continuous cropping obstacles; tolerance; nutrients DOI: 10.25165/j.ijabe.20251806.9260 Citation: Chen D Y, Jiang X R, Xu X J, Wang J D, Zhang Y C, Ma J Z, et al. Comparative analysis of continuous cropping tolerance and nutrient status of three types of sweet potatoes. Int J Agric & Biol Eng, 2025; 18(6): 56–65.